Formation of High School Students’ Readiness for Effective Conflict Resolution - Ismoilovna, Tillayeva Munisaxon (European Journal of Life Safety and Stability (2660-9630), 2022)
The article points out the need to use along with effective destructive conflicts in terms of content in order to educate and improve the personality of senior schoolchildren. The author analyzes the approaches used in conflict logy, presents and outlines his own classification of typical conflicts, notes the peculiarities of their origin, formation and resolution among high school students. The psychological and pedagogical mechanisms of translating everyday, mostly destructive conflicts into positive ones are revealed, the pedagogical skill of fruitful conflict resolution in high school age is presented.